Relationship between allergic transfusion reactions and allergic predisposition among pediatric patients with hematological/oncological disease. Issue 5 (16th March 2022) - Yanagisawa, Ryu; Ishimine, Nau; Komori, Kazutoshi; Kurata, Takashi; Saito, Shoji; Tanaka, Miyuki; Sakashita, Kazuo; Tozuka, Minoru; Nakazawa, Yozo
Abstract: Background: Allergic transfusion reactions (ATRs) manifest frequently as transfusion reactions, and their onset may be related to a patient's allergic predisposition. Moreover, although pediatric patients with hematological/oncological disease are more susceptible to ATRs, the relationship between allergic predisposition and ATRs remains to be fully clarified. Study Design and Methods: Patients who were diagnosed with pediatric hematological/oncological disease and received transfusion at the study institutions were included. We determined patient background information related to their allergy history, measured the levels of allergen‐specific immunoglobulin E (IgE) using sera obtained on diagnosis, and analyzed their associations with ATR onset. Results: Of the 363 patients analyzed, 144 developed ATRs. Multivariate analysis identified cases with high basophils in the peripheral blood, and Dermatophagoides pteronyssinus – and egg white–specific IgEs were involved in the development of ATR in all age groups. Meanwhile, a history of food allergies, and positivity for Japanese cypress‐ and D. pteronyssinus ‐specific IgEs were risk factors for developing ATRs in the <5 years age group. Moreover, patients aged 5–<10 years with a history of asthma, allergic rhinitis, pollinosis, or atopic dermatitis, and those aged ≥10 years with positivity for dog dander‐specific IgE were at risk for developing ATRs. Conclusion: The allergic constitution of patients plays a role in ATR onset even in pediatric hematological/oncological diseases. Therefore, advance confirmation of a patient's allergic constitution may partly predict the onset of ATRs. However, since multiple allergic predispositions within complex mechanisms may be involved in the onset of ATRs, further verification is required.